Towards an integrated case method in management education-developing an ecosystem-based research and learning journey for flipped classrooms - Jan-Philipp Büchler; Gregor Brüggelambert; Haijing Helen de Haan-Cao; Roger Sherlock; Asta Savanevičienė (Administrative Sciences, 2021)
In the field of management science and business administration, the case method is gaining ground in research and in teaching. Case studies support on the one hand exploratory research and on the other hand problem-based teaching. However, we find that case research and case teaching remain unchained in management study programs and propose to close this gap. We identify an untapped potential of boosting the case method by integrating case-based research and teaching into a discovery and learning journey of applied science. We suggest embedding the "integrated case method" (ICM) in the ecosystem of universities, with the aim of enhancing and intensifying the knowledge transfer between business and the higher educational sector, thereby achieving better learning objectives in higher education. As a result, this approach enables the development of a high level of contextual intelligence and thus helps to avoid the fallacies of teaching based on uniform theoretical content.
Keywords: 350; case method; contextual intelligence; knowledge transfer; learning journey; management education